2019
DOI: 10.1111/mec.14973
|View full text |Cite
|
Sign up to set email alerts
|

Novel microRNAs are associated with population divergence in transcriptional response to thermal stress in an intertidal copepod

Abstract: The role of gene expression in adaptation to differing thermal environments has been assayed extensively. Yet, in most natural systems, analyses of gene expression reveal only one level of the complexity of regulatory machineries. MicroRNAs (miRNAs) are small noncoding RNAs which are key components of many gene regulatory networks, and they play important roles in a variety of cellular pathways by modulating post‐transcriptional quantities of mRNA available for protein synthesis. The characterization of miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 103 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…The recovery treatment involved transferring copepods from anoxia vials into culture plates with normoxic water. RNA isolation, mRNA library preparation, sequencing, and data processing were performed as described previously (44) ( SI Appendix ). Differential gene expression at each time point was quantified with edgeR by comparing anoxia samples to their respective normoxia control group and assessed with a false discovery rate of 0.10.…”
Section: Methodsmentioning
confidence: 99%
“…The recovery treatment involved transferring copepods from anoxia vials into culture plates with normoxic water. RNA isolation, mRNA library preparation, sequencing, and data processing were performed as described previously (44) ( SI Appendix ). Differential gene expression at each time point was quantified with edgeR by comparing anoxia samples to their respective normoxia control group and assessed with a false discovery rate of 0.10.…”
Section: Methodsmentioning
confidence: 99%
“…Even after many generations of laboratory rearing, previously published work has consistently resolved latitudinal variation in upper thermal tolerance among T. californicus populations with a significant correlation between tolerance and variation in maximum habitat air temperatures (Willett, 2010;Kelly et al, 2012;Pereira et al, 2017;Leong et al, 2018;Willett & Son, 2018;Healy et al, 2019). Population differences in tolerance have been most clearly linked with differences in the expression of molecular chaperones, such as heat-shock proteins, during and following heat stress (Schoville et al, 2012;Kelly et al, 2017;Graham & Barreto, 2019;Tangwancharoen et al, 2018Tangwancharoen et al, , 2020Healy et al, 2019;, and knockdown of heat-shock protein beta 1 reduces the maximum temperature that these copepods can tolerate (Barreto et al, 2015). In addition to the important role of molecular chaperones, recent studies have proposed that loss of mitochondrial ATP synthesis capacity at high temperatures may also be associated with tolerance limits in T. californicus Healy et al, 2019).…”
Section: Main Textmentioning
confidence: 99%
“…The correlation between losses of ATP synthesis capacity at high temperatures and upper thermal limits in T. californicus adds an additional mechanism of thermal adaptation to the substantial evidence linking heat-shock protein (hsp) expression and function with upper thermal tolerance in this species. Expression levels of many hsps increase as a result of acute heat stress in laboratory-reared T. californicus from both within-and between-population crosses (Schoville et al, 2012;Kelly et al, 2017), and variation in the extent of hsp induction during heat stress has been positively associated with upper thermal limits among populations (Schoville et al, 2012;Graham & Barreto, 2019;Tangwancharoen et al, 2018Tangwancharoen et al, , 2020. Similarly, variation in upper thermal tolerance due to differences in rates of warming during acute temperature exposures or in developmental temperatures are also positively associated with variation in hsp expression Healy et al, 2019).…”
Section: Main Textmentioning
confidence: 99%
“…This variable expression between populations can cause intraspecific variation in morphology (Arif et al 2013) or epigenetic regulation (Zhai et al 2008), but the adaptive significance of this variation is usually uncharacterized. However, a few studies have identified differential microRNA expression between natural populations with known local adaptations, such as to heat stress (Graham and Barreto 2019) or hydrogen sulphide toxicity (Kelley et al 2021), providing a link between microRNA-mediated gene regulation and locally-adaptive phenotypes. While much is unknown about how endo-siRNAs may be involved in local adaptation compared to microRNAs, the regulatory role of some endo-siRNAs in mediating responses to environmental stress (Wu et al 2020) suggests that environmental differences between populations could lead to adaptive evolution in endo-siRNA pathways.…”
Section: Introductionmentioning
confidence: 99%